Phytopharmaceuticals: An emerging platform for innovation and development of new drugs from botanicals - Bhusnure, Omprakash G; Shinde, Madhuri C; Vijayendra, Swamy S.M; Gholve, Sachin B; Giram, Padmaja S; Birajdar, Mahesh J (Journal of Drug Delivery and Therapeutics, 2019)
A phytomedicine, or phytopharmacutical, is a complex mixture derived from plant sources that is used as a medicine or drug. The Ministry of Health has begun the standardization of the names of all phytopharmaceutical preparations. The development of phytopharmaceutical products, which might partially substitute some of the conventional medications demanding imported raw materials, and which could be produced by pharmaceutical industries based in developing countries through joint projects. Highest demands are made on clinically proven phyto-pharmaceuticals. Their effect and safety have to be verified in randomized, double-blind, (placebo)-controlled clinical trials. They are developed and scientifically evaluated in the same way as conventional medicinal products. Globally, herbal medicine has been considered an important alternative to modern allopathic medicine. While they have become very popular, only select herbs have been scientifically evaluated for their potential in medical treatment. The new drug Veregen (Polyphenon E) Ointment is the first prescription botanical (herbal) drug approved by the U.S. FDA under the “new” drug amendments of 1962 that required drugs to be proven safe and effective prior to being marketed in the U.S. Because of the unique health benefits and relatively low side effects, natural products such as food/dietary supplements, nutraceuticals and herbal medicines have been gaining popularity all over the world The gap between the popularity of these remedies and the frequently weak scientific basis of their use is striking. In reality, the efficacy and true frequency of side effects for most herbal medicine products is not known because the majority have not yet been tested in large clinical trials and because pharmacovigilance systems are much less extensive than those in place for pharmaceutical products. In contrast to the popularity of herbal medicinal products, physicians and consumers often have a very critical view of robust efficacy and safety profiles. Application of pharmaceutical nanotechnology for plant actives and extracts, is gaining a tremendous growth and interest among the scientist. Keywords: Phytopharmaceuticals, Harbal, plant extract, phototherapy, Morphine, Ayurveda, metabolites, fingerprint.